Mempertanyakan Sepuluh Tahun Pengukuran Kemampuan Berpikir Spasial dalam Penelitian Pendidikan Geografi di Indonesia (2013-2023) - Al-Bukhori, Lucky Airlangga; Purwanto, Purwanto (Jayapangus Press, 2025)
The measurement of spatial thinking skills (KBS) in Indonesia requires adjustments to align with the historical context and local conditions. In geography education, the measurement of KBS generally focuses on the dimension of spatial relationships, although research shows that KBS encompasses various distinct spatial skills. Testing for specific skills does not necessarily reflect other spatial abilities, and the significant differences in measurement methods often lead to inconsistencies in findings. Furthermore, KBS research in Indonesia is not connected to its development context in Western countries and has not undergone a structured adaptation to the local culture and environment. This study aims to map the test instruments used and evaluate the practices of measuring KBS in geography education in Indonesia. The literature review follows the PRISMA 2020 procedure, as adapted by the author, with 100 articles meeting the criteria, including 28 conference papers and 72 journal articles. Most studies employ instruments developed independently, while standardized instruments for repeated use are rarely applied. KBS test instruments can be classified into seven types with two approaches. The measurement of KBS is conducted with descriptive, causal, interrelational, and instrument development objectives. Despite the variation in measurement methods, the conclusions drawn tend to be uniform, which necessitates scrutiny of the content validity of the instruments. Additionally, the measurement of KBS is often limited to the dimension of spatial relationships, with research directions being difficult to map due to the unstructured adaptation process. This study recommends reaching a consensus on the concepts, methodologies, and measurement standards that align with the local needs in Indonesia.